2021
DOI: 10.1002/app.50959
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tensile behavior and molecular structure of the thermoplastic polyurethane sheets injection molded at different mold temperatures

Abstract: This paper aims to investigate the influence of the mold temperature on the mechanical responses at different ambient temperature and molecular structure of the injection molded TPU sheets. The tensile properties of the TPU sheets prepared at different mold temperatures were obtained at different ambient temperatures. As the mold temperature increases, both the elongation at break and tensile strength of the specimens increase. The specimens show yield behavior during stretching at −30 and −50°C. The microstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The general results show that with the increase in mold temperature, the mechanical properties of polyurethane foams materials such as compression, tensile, shear strength and elastic modulus have a significant decreasing trend. Furthermore, Xiang [ 47 ] investigated the effect of mold temperature (40 °C, 60 °C, 80 °C, 100 °C) on the mechanical response of injection molded polyurethane foams materials at different ambient temperatures and molecular structures, and the stress–strain curves obtained indicated that the increase in mold temperature led to a decrease in tensile strength, as well as tensile modulus and an increase in tensile yield strain. Some scholars have come to different conclusions.…”
Section: Influence Of Temperature On Polyurethane Foam Properties Dur...mentioning
confidence: 99%
“…The general results show that with the increase in mold temperature, the mechanical properties of polyurethane foams materials such as compression, tensile, shear strength and elastic modulus have a significant decreasing trend. Furthermore, Xiang [ 47 ] investigated the effect of mold temperature (40 °C, 60 °C, 80 °C, 100 °C) on the mechanical response of injection molded polyurethane foams materials at different ambient temperatures and molecular structures, and the stress–strain curves obtained indicated that the increase in mold temperature led to a decrease in tensile strength, as well as tensile modulus and an increase in tensile yield strain. Some scholars have come to different conclusions.…”
Section: Influence Of Temperature On Polyurethane Foam Properties Dur...mentioning
confidence: 99%
“…Regarding to the Young's modulus, for the common TPUs, it usually falls in the range of 1.5–30.0 MPa based on their chemical nature and processing conditions 38,39 . However, the graphene‐based tPU nanocomposites showed a relatively high modulus, which falls in the range of 38.5–96.2 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding to the Young's modulus, for the common TPUs, it usually falls in the range of 1.5-30.0 MPa based on their chemical nature and processing conditions. 38,39 However, the graphene-based tPU nanocomposites showed a relatively high modulus, which falls in the range of 38.5-96.2 MPa. The high modulus of the specimens is due to the presence of graphene nanoparticles with 0.50 wt.%, which is in accordance with the Young's modulus of TPU/graphene nanocomposites.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It was revealed by observing the morphological changes during the separation process that the PE layer was divided into two parts, indicating that cohesive damage occurred in the PE body, and the stresses within the PE layer changed. [35,36] This provided a reference for the selection of the joining strength of the integrated structure according to the elastic modulus of the material.…”
Section: Tensile Forcementioning
confidence: 99%